Everybody, move your feet! - Huelin, Jodi. (New York : Collins, 2010)
Sid plans a weekend of doing nothing but watching television, but soon changes his mind after he learns the importance of daily physical exercise.
K-3
Accelerated Reader AR
Keywords: Physical fitness; Exercise; Health